Evaluation of natural gas hydrates as a future methane source. (2nd July 2016) - Demirbas, Ayhan; Rehan, Mohammad; Al-Sasi, Basil Omar; Nizami, Abdul-Sattar
ABSTRACT: In recent years, attention has been given to obtaining methane gas from natural gas hydrates (NGHs) sediment; but its production, economics, and safety are still far away from being commercially viable for many years, and so more research is needed. NGHs are nonstoichiometric crystalline solid compounds that form from mixtures of water molecules and light weight natural gases such as methane, ethane, propane, and carbon dioxide. They are formed in specific thermodynamic conditions, low temperatures (5–15°C) and high pressures (2–3 MPa), and are found in (a) onshore polar regions beneath permafrost and (b) offshore deep-sea sediments. Methane, NG, is the cleanest fossil fuel and its huge amounts in NGHs have carbon quantities more than double of all fossil fuels. The methods that have been proposed for NG extraction from NGHs include: (a) depressurization, (b) thermal stimulation, and (c) chemical inhibitor injections. The authors review the potential of methane gas from NGHs as an unconventional source of future energy. The formation of NGHs as well as extraction of methane from NGHs coupled with technical and environmental challenges are also addressed.